Synergistic Effect of Biochar and Organic Fertilizers on Tomato Growth, Fruit Quality, and Yield in Heavy Metals-Contaminated Soil - Ali, Qazi Shoaib; Alam, Mehboob (Indus Journal of Bioscience Research, 2025)
This study presents a novel, integrative approach to remediating heavy metal-contaminated soils by evaluating the synergistic effects of biochar in conjunction with multiple organic fertilizers such as farmyard manure (FYM), spent mushroom compost (SMC), and leaf mould (LM) on the growth, yield, and fruit quality of tomato (Solanum lycopersicum). Unlike previous research, which has predominantly assessed these amendments in isolation, our work systematically explores their combined application, offering new insights into their interactive effects on both plant productivity and heavy metal mitigation. The experiment was conducted at the Agriculture Research Station (Merged Areas) District Bajuar during the 2022 and 2023 growing seasons, utilizing a randomized complete block design (RCBD) with two factors: biochar applied at 0.0%, 1.0%, 1.5%, and 2.0% (w/w), and organic fertilizers (FYM, SMC, LM) at 2% and 3% (w/w) concentrations. Tomato seedlings (cv. Rio Grande) were transplanted into soils sourced from mining-affected sites, characterized by elevated levels of heavy metals. Results demonstrated that biochar application, particularly at 2%, significantly improved key agronomic and quality parameters, including plant height (67.53 cm), leaf area (41.68 cm2), and yield (9.45 t ha⁻¹). Notably, biochar treatments also enhanced ascorbic acid, lycopene, and carotenoids, while markedly reducing the accumulation of toxic metals in fruit tissues (2.55 mg kg-1), which remains within the maximum permissible limit set by the WHO. Organic fertilizers further contributed to these improvements, with 3% FYM yielding the highest plant height and fruit yield, and 3% SMC optimizing ascorbic acid, total phenolic content, and lycopene levels alongside a pronounced reduction in fruit heavy metal concentrations (2.39 mg kg-1) which remains within the maximum permissible limit set by the WHO. The combined application of 2% biochar with 3% FYM resulted the most substantial gains in plant growth and yield, whereas the pairing of 2% biochar with 3% SMC maximized fruit quality indices.This dual amendment strategy showed better results than using biochar or organic fertilizers alone, clearly demonstrating a synergistic effect in increasing tomato yield and reducing heavy metal uptake. The results highlight that applying 2% biochar together with 3% organic fertilizer (either FYM or SMC) is an effective and sustainable way to boost tomato growth, quality, and yield while minimizing heavy metal contamination in polluted soils.